PHYTOCHEMICAL EVALUATION OF Terminalia catappa Linn. FOR BIOMEDICINAL AND NUTRITIVE PURPOSES - Fakorede, C. O.; Odega, C. A.; Anguruwa, G. T. (RENEWABLE, 2024)
Terminalia catappa is a perennial tree species that has been introduced in gardens, parks and farmlands as an ornamental and shade tree, sand-dune stabilizer and source of fuelwood. This study assessed the qualitative and quantitative characteristics of phytochemicals present in the leaves and bark of T. catappa. It discussed the medicinal and nutritive potentials of the leaves and bark. Nine metabolites (alkaloids, flavonoids, saponins, tannins, anthraquinones, terpenoids, cardiac glycosides, phenols and steroids) were identified in the leaves while two of the metabolites were absent in the bark (anthraquinones and steroids). The alkaloids content (36.65% and 35.15%) was highest, followed by saponins (2.90% and 2.25%) and terpenoids (0.25% and 0.60%) in leaves and bark. Similarly, flavonoids (19.69 µg and 15.72 µg) were highest, followed by tannins (4.23 µg and 2.83 µg) and phenols (2.07 µg and 1.76 µg) in leaves and bark, respectively. The phytochemicals are capable of fighting oxidative stress and possess therapeutic properties that could be potentially explored in drug discovery.